Under-reporting of deaths limits our understanding of true burden of covid-19. (12th October 2021) - Whittaker, Charles; Walker, Patrick G T; Alhaffar, Mervat; Hamlet, Arran; Djaafara, Bimandra A; Ghani, Azra; Ferguson, Neil; Dahab, Maysoon; Checchi, Francesco; Watson, Oliver J
Abstract : Charles Whittaker and colleagues argue that accurate mortality data are essential for a fair, just, and equitable response to pandemics and suggest how to obtain them